DAMPAK REMITEN MIGRAN INTERNASIONAL TERHADAP PENINGKATAN USAHA PRODUKTIF - Evita Soliha Hani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
The objectives of the study are to find out the influence of migrant success towards remittance in East Java and the influence of the remittance towards the improvement of productive business’s income. The study was conducted in East Java. There were 120 respondents of international migrant departing in their village. The methods to analyze are descriptive and analytic. The analysis applied is multiple linear regressions. The results showed that (1) the success of international migrants is a positive effect on remittances. The average international migrant remittances from the success of Rp 19.5 million per year and (2) remittances positively affect (a) total revenue earning venture, (b) farm business income, and (c) interests. The suggestions that may be recommended are international migrants may increase remittances to their families in order to increase their earning business income, thereby increasing the welfare of the family.Key Words: Remittance, International Migrant, Productive Business